TLC The Low Countries : Arts and Society in Flanders and The Netherlands. - Devoldere, Luc; Aarsman, Hans; Bachrach, Fred G. H.; Blyth, Derek; Bolkestein, Frits; Broucke, Koen; Buelens, Geert; Chielens, Wim; Christiaens, Tom; De Vos, Johan; Depoortere, Johan; Deunk, Gerritjan; et al. (Rekkem : Stichting Ons Erfdeel, 2004)
Panamarenko ; Van Mieghem, Eugène ; Moesman, Johannes Hendrikus ; Körmeling, John ; Lafontaine, Marie-Jo ; Van Severen, Maarten ; Kelley, Mike ; Boonstra, Marjoleine ; Appel, Karel ; Kaap, Gerald Van Der ; Van Severen, Dan ; Andriesse, Emmy ; Corbijn, Anton ; Coenen, Jo
boek
Keywords: België; Nederland; Vlaanderen